Victorian Brick Sewers for a Clean Flowing Colonial City. Issue Volume 172:Issue EH 3(2019:Aug.) (19th August 2019) - Dey, Ayanangshu; Downey, Declan
Abstract : Effort on providing an organised sanitation and drainage facility for Calcutta's annual inundation events during monsoon and high tides in river Hooghly was initiated by Lord Wellesley in 1803. Subsequently, Lottery committee (1809) and Fever Committee (1840) worked on relieving the city from its water logging and sanitation problems. Its extremely unhygienic sanitary conditions, filthy status of drains, high rate of disease propagation, and sickness could only be compared to the infamous 'Great Stink' of London (1858). Contemporary to the works being executed by Sir Joseph Bazalgette for developing London's central sewerage system, Calcutta's first brick sewer system was adopted for construction in 1858 and was commissioned in 1868. Several sanitation schemes were proposed, but the one put forward by William Clark was taken up following extensive review. Calcutta witnessed the golden era of large diameter brick sewer construction over following decades. By 1890, Calcutta was provided with almost 300 km of centralised sewer network. This paper documents the history of development of this combined sewerage and drainage system, oldest stretches of which were recently rehabilitated.